Performance Evaluation of Sfbc-Ofdm System Using Zero-Forcing Detection Scheme Under Mobile Environment - Kaur, Mandeep (My University, 2014)
Fading is an important issue when communication has to be done via wireless channel in mobile environment. Since the behaviour of the multipath wireless channel is such that the amplitude and power of the received signal is random, therefore Rayleigh fading model is used to model the characteristics of the channel. The other important technique which is widely used nowadays is Orthogonal Frequency Division Multiplexing (OFDM), which reduces the effect of frequency selective channel by dividing the data stream that is to be transmitted into multiple parallel channels and the channel is thus divided into number of parallel narrowband sub channels such that each sub channel has lower data rate. Thus, OFDM converts the frequency selective fading to approximate flat fading. However, OFDM is more popular due to its easy implementation using Discrete Fourier Transform (DFT). Moreover, OFDM is bandwidth efficient because parallel subcarriers are orthogonal to each other and thus no interference occurs. However, there are many other issues such as Inter-Block interference (IBI) and Inter-carrier interference (ICI) which may affect the system performance in mobile environment. By using cyclic prefix (CP), the IBI can be eliminated completely but to remove ICI, channel estimation has to be performed accurately which further increases the complexity of the receiver. The other most important strategy used by wireless communication systems is known as Multiple Input Multiple Output (MIMO) which enhances the quality as well as data rate of the system. By transmitting data over MIMO channels, maximization of data rate or diversity has been ensured. So, space-time or space-frequency block coding is used with OFDM systems which further helps in getting better bit error rate performance over the frequency selective channels. Further, the data rate can be improved by employing MIMO with the above mentioned technique. In this thesis, we have made an effort to study space-frequency block-coded OFDM under frequency selective fading environment. We have presented a scheme, which employs a low complexity zero-forcing (ZF) receiver in wireless fast fading channel where channel response is not same for the adjacent subcarriers. The bit error rate performance of low complexity receiver has been compared to the classical ZF receiver and the matched filter (MF) receiver, which shows that the low complexity receiver outperforms the MF receiver in fast fading mobile environment and performs well against classical ZF receiver. Moreover, application of the low complexity receiver reduces the computational complexity nearly to half when compared to ZF receiver, as it eliminates the use of pseudo-inversion method of channel matrix for the higher spatial diversity schemes.
ME, ECED
Keywords: Space-Frequency Block Coding (SFBC); Inter carrier interference (ICI); Inter block interference (IBI); frequency selectivity; Zero-Forcing (ZF); Matched Filter (MF)